Comparative Study on Extreme Heat between Guadalquivir Valley and Segura River Valleys: Trend and High Resolution Cartography - David Espín-Sánchez; Carmelo Conesa-García (Revista de Estudios Andaluces, 2018)
The Guadalquivir and Segura Valleys are geographical areas in the south of the Iberian Peninsula where extreme summer temperatures have great recurrence of extremely high values, especially during the last summers. A comparison of the characteristics of extreme heat between the two zones is proposed, analyzing the statistical trend (1900-2017) of the cities of Seville and Murcia and a detailed cartography of the warm poles of maximum and minimum temperatures is provided using high resolution modeling tools (AROME 1.3 km) and remote sensing (MYD11A1). The results are conclusive, since there is a statistically significant increase of the days with extreme heat indices (TX35, TX40 and TN20), while periods of warm spells (WSDI) increase in recurrence and duration